Case study of Gyzyl Suw settlement, Turkmenistan hunting and its consequencies : social implications - Ovezdurdyyev, Ruslan; Schmidt-Vogt, Dietrich; Shrestha, Rajendra Prasad; Shipin, Oleg V.; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Community based Natural Resource Management was seen as a reality in the location of the study site. However, the realities oftentimes differ from the perceptions. Overestimated capacities of the community came up as a major cause of inability to successfully implement an introduction of the community natural resource management in the locality. The community still suffers from the outdated, established during the soviet times approaches towards the use of the natural reserves added up by a number of additional circumstances that appeared either naturally or enforced by the people over the times. The communities as well as the government authorities lack an appropriate set of laws to regulate the hunting rates and improve social conditions of the community. However, the economic and social conditions are more or less identical in most of the rural areas of Turkmenistan. The research describes the interrelations between the community and government as well as within the community itself with an emphasis to the hunting as a major source of income generation, due to the lack of adequate infrastructure and alternative sources of income generation that spreads to almost all rural parts of the country.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Fowling -- Turkmenistan; Protected areas -- Turkmenistan